FMCW Miniature Radar System for Aerospace and Avionics Applications (Development Engineering Conferences Center Articles Database, 2026)
Frequency Modulated Continuous Wave (FMCW) radar technology has emerged as a cornerstone solution for miniature radar systems in aerospace and avionics applications. This paper presents a comprehensive analysis of FMCW miniature radar systems, covering fundamental operating principles, architectural design, implementation challenges, and diverse applications. The FMCW technique offers significant advantages including high range resolution, low peak power requirements, and compact form factor, making it ideal for space-constrained platforms such as CubeSats, unmanned aerial vehicles (UAVs), and small aircraft. We examine the mathematical foundations of chirp signal generation, range-Doppler processing, and resolution limits. Key architectural components including RF front-end design, antenna configurations, and digital signal processing are analyzed. Critical challenges such as phase noise, nonlinearity, and thermal management are discussed with practical mitigation strategies. A comparative analysis with pulsed radar systems highlights the trade offs and advantages of FMCW technology. Applications spanning satellite remote sensing, collision avoidance, terrain mapping, and autonomous navigation are explored. This work provides aerospace engineers and researchers with a thorough understanding of FMCW miniature radar technology and its implementation considerations.